Evaluation of the spatial variability of the elements in tree barks used as biomonitors of atmospheric pollution (Brazilian Journal of Radiation Sciences, 2021)
Tree barks have proven to be a valuable source of information on air quality. Nowadays, studies with this biomonitor are constantly being developed. However, data of several factors that affect the accumulation of the pollutants in the barks, such as bark porosity, duration of the deposition on the bark and dispersion or variability of pollutants in a defined area, are scarce in the literature. The aim of this study was to evaluate the spatial variability of chemical elements concentrations accumulated on Sibipiruna (Cenostigna pluviosarum) barks in order to examine their aerial dispersion in two small urban areas of the Metropolitan Area of São Paulo. The neutron activation analysis (NAA) applied in the analyses consisted of irradiation the aliquots of the sample together the synthetic element standards at the IEA-R1 nuclear reactor. Concentrations of the As, Br, Ca, Co, Cr, Cs, Fe, K, La, Mn, Rb, Sb, Sc, V and Zn were determined in tree barks using short and long irradiations. Results obtained in the analyses of the tree bark samples indicated that the variability of element concentrations depends on the element, study area and numbers of trees. The variability of element concentrations in general was higher for elements presenting low concentrations. Quality control of the analytical results was evaluated by the analysis of INCT-MPH-2 Mixed Polish Herbs Certified Reference Material and these results presented good accuracy with values of standardized difference or |ζ score| ≤ 2, indicating that the procedure of NAA applied is suitable for the analyses.